Amyotrophic lateral sclerosis: one or multiple causes? - Aline Furtado Bastos; Marco Orsini; Dionis Machado; Mariana Pimentel Mello; Sergio Nader; Júlio Guilherme Silva; Antonio Marcos da Silva Catharino; Victor Hugo Bastos; Alessandra Pereira; Luciane Lacerda Pessoa; Flavio R. Sztajnbok; Marco Araújo Leite; et al. (MDPI AG, 2011)
The Amyotrophic lateral sclerosis (ALS) is the most common form of motor neuron disease in the adulthood, and it is characterized by rapid and progressive compromise of the upper and lower motor neurons. The majority of the cases of ALS are classified as sporadic and, until now, a specific cause for these cases still is unknown. To present the different hypotheses on the etiology of ALS. It was carried out a search in the databases: Bireme, Scielo and Pubmed, in the period of 1987 to 2011, using the following keywords: Amyotrophic lateral sclerosis, motor neuron disease, etiology, causes and epidemiology and its similar in Portuguese and Spanish. It did not have consensus as regards the etiology of ALS. Researches demonstrates evidences as regards intoxication by heavy metals, environmental and occupational causes, genetic mutations (superoxide dismutase 1), certain viral infections and the accomplishment of vigorous physical activity for the development of the disease. There is still no consensus regarding the involved factors in the etiology of ALS. In this way, new research about these etiologies are necessary, for a better approach of the patients, promoting preventive programs for the disease and improving the quality of life of the patients.